PEMBERIANABUBOILER DAN FOSFAT ALAM TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Hendi Erwandi; Nelvia '; Wawan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Oil palm (Elaeis guineensis Jacq.) is one of the higher multi-purpose crop in the plantation sector in Indonesia, especially Riau Province. To support the growth and development of oil palm seedlings needed a good planting medium that serves as a place of growth and development of roots and place the plant absorb nutrients and water. One of them is the provision of boiler ash and phosphate as well as utilize the peat soil as a medium. This study aims to determine the effect of boiler ash and rock phosphate on the growth of palm oil (Elaeis guineensis Jacq) in the main nursery. The design used in this research is completely randomized design (CRD) factorial consisting of two factors. The first factor is the provision of boiler ash treatment with 4 levels. The second factor is the natural phosphate treatment with 4 levels and each unit is repeated 3 times. The study states that increased doses of boiler ash and rock phosphate given to plant oil palm seedlings showed no significant effect on plant height increase, in the number of leaves, the increase in diameter tubers, plant dry weight and ratio root crown.   Keywords: Abu Boiler, Phosphate, Oil Palm